Dampak Penerapan Etika Bisnis Islam Terhadap Penjualan: (Studi Kasus Pelaku Muslim Di Pasar Sukowono) - Yassir Arafat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
Buying and selling must not be done based on one's own wishes and methods which can cause harm to other people. Islam is always based on values ​​and ethics in all aspects of human life as a whole, including discourse on buying and selling, however buying and selling has regulations in Islamic law which are sourced from the Qur'an and Sunnah. Based on the background above, the author is interested in studying further by conducting a scientific research entitled: